MULTICULTURAL ISLAMIC RELIGIOUS EDUCATION AS A COUNTER-NARRATIVE STRATEGY AGAINST RELIGIOUS EXTREMISM IN SCHOOLS - Rochmad Basuni (Journal Of Islamic Education And Pesantren, 2022)
This article aims to analyze the integration of critical pedagogy into multicultural Islamic Religious Education (PAI) as a counter-narrative strategy against religious extremism in schools. The study is grounded in the growing polarization of religious identities and the infiltration of exclusivist narratives within educational spaces, while Islamic education practices often remain normative and doctrinal with limited dialogical engagement. Employing a qualitative approach with a critical case study design, this research explores classroom practices that incorporate reflective dialogue, social problem-posing, and the deconstruction of exclusivist religious narratives. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using an interactive model of data reduction, display, and conclusion drawing. The findings reveal that integrating critical pedagogy transforms Islamic education classrooms into dialogical spaces that foster students’ reflective awareness of intolerance and extremism. The counter-narrative strategy operates through three main stages: problematizing social realities, deconstructing absolutist claims, and reconstructing inclusive religious understanding. Theoretically, this study expands the discourse on multicultural Islamic education by incorporating a critical-reflective dimension as an epistemological framework for strengthening religious moderation in schools. The results indicate that critical pedagogy within multicultural Islamic education serves as a transformative praxis to cultivate moderate consciousness and prevent the reproduction of extremist narratives in educational settings